2019
DOI: 10.3389/fnins.2019.00743
|View full text |Cite
|
Sign up to set email alerts
|

Altered Regional Homogeneity in Patients With Corneal Ulcer: A Resting-State Functional MRI Study

Abstract: Objective To investigate the potential regional homogeneity (ReHo) brain activity changes in patients with corneal ulcer (CU) and their possible relationship with clinical symptoms. Materials and Methods Forty patients with CU (26 men and 14 women), and 40 healthy controls (HCs) (26 men and 14 women) closely matched in age, sex, and weight underwent resting-state functional MRI scans, respectively. The ReHo method was applied to evaluate synchronous neural activity chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…In the present study, ROC analysis was applied to determine the reliability of using ReHo values to diagnose patients. Several neuroimaging studies focusing on ocular diseases have successfully applied ROC analyses to discriminate those with ocular disease from NCs [ 11 , 22 , 24 , 49 , 50 ]. According to these studies, the ability to discriminate conditions are considered excellent, moderate, fair, and failed when AUC values are 0.9–1, 0.7–09, 0.5–0.7, and less than 0.5, respectively [ 22 , 24 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, ROC analysis was applied to determine the reliability of using ReHo values to diagnose patients. Several neuroimaging studies focusing on ocular diseases have successfully applied ROC analyses to discriminate those with ocular disease from NCs [ 11 , 22 , 24 , 49 , 50 ]. According to these studies, the ability to discriminate conditions are considered excellent, moderate, fair, and failed when AUC values are 0.9–1, 0.7–09, 0.5–0.7, and less than 0.5, respectively [ 22 , 24 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common method of noise reduction is smooth. The smooth method is also used in previous studies on ophthalmic diseases (Chen et al, 2017 ; Wang et al, 2017 ; Xu et al, 2019 ). The time series were further linearly detrended and temporally band-pass filtered (0.01–0.08 Hz).…”
Section: Methodsmentioning
confidence: 99%
“…Previous researches showed that patients with DED had extensive alterations in brain function, and abnormal brain function played an important role in the maintenance and development of dry eye symptoms (Rahman et al, 2015 ; Levitt et al, 2017 ). fMRI has been used to explore abnormal functional activity in eye diseases such as glaucoma, amblyopia and corneal ulcers (Lin et al, 2012 ; Li et al, 2014 ; Rahman et al, 2015 ; Chen et al, 2017 ; Wang et al, 2017 ; Xu et al, 2019 ). However, it remains unclear whether patients with DED have abnormal GFC in certain brain regions.…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that patients with CU had markedly increased regional homogeneity (ReHo) values in the left middle frontal gyrus. 22 In addition, activation of FEF was reported in magnetic resonance studies of retinal detachment, 23 age-related macular degeneration, 24,25 progressive retinitis pigmentosa, 26 and macular hole 27 retinalrelated diseases. Consistent with previous studies, the increased FC values between the bilateral V1 and left and right middle frontal gyri shown in this study reflected the activation of visual processing, suggesting the plasticity that compensates for CU-related visual input deficits.…”
Section: Analysis Of Increased Fc Values In the Cu Groupmentioning
confidence: 97%